European Union Security Dynamics - Matlary, J. author. aut Link
XIII, 234 p. 1 illus.
Keywords: This book shows how France and Britain are leaders in EU security and defense policy, and explains why both states need each other in this policy area. The lack of relevant military capacity in Europe today implies that the US favors a strong EU in this field.